Counterexamples to F. Morel’s conjecture on $\protect π _0^{\protect \mathbb{A}^1}$ - Ayoub, Joseph (Comptes Rendus. Mathématique)
We exhibit counterexamples to F. Morel’s conjecture on the $\mathbb{A}^1$-invariance of the sheaves of connected components of $\mathbb{A}^1$-local spaces.